A green and environmentally benign route to synthesizing Z-scheme Bi2S3-TCN photocatalyst for efficient hydrogen production - Yuan, Lang; Yin, Yihang; Xiang, Peng; Shao, Yugui; Gao, Jie; Liu, Jianan; Meng, Huiyuan; Li, Li; Xie, Ying; Xiao, Xudong; Jiang, Baojiang (Frontiers in Chemistry, 2024)
Designing and developing photocatalysts with excellent performance in order to achieve efficient hydrogen production is an important strategy for addressing future energy and environmental challenges. Traditional single-phase photocatalytic materials either have a large bandgap and low visible light response or experience rapid recombination of the photogenerated carriers with low quantum efficiency, seriously hindering their photocatalytic applications. To solve these issues, an important solution is to construct well-matched heterojunctions with highly efficient charge separation capabilities. To this end, an in situ sulfurization reaction was adopted after the deposition of Bi3+ supramolecular complex on a layered supramolecular precursor of tubular carbon nitride (TCN). X-ray diffraction (XRD) patterns confirmed that the as-prepared sample has a good crystalline structure without any other impurities, while high-resolution transmission electron microscopy (HR-TEM) revealed that the heterojunction possesses a 2D structure with a layer of nano-array on its surface. Combined Fourier-transform infrared (FT-IR) spectra and energy-dispersive X-ray spectroscopy (EDX) revealed the interfacial interactions. Owing to the formation of the Z-scheme heterojunction, the visible light adsorption and the separation efficiency of the photo-generated carriers are both obviously enhanced, leaving the high energy electrons and high oxidative holes to participate in the photocatalytic reactions. As a result, the photocatalytic hydrogen evolution rate of Bi2S3-TCN achieves 65.2 μmol g-1·h-1. This proposed green and environmentally benign route can also be applied to construct other sulfides with 2D TCN, providing some important information for the design and optimization of novel carbon-nitride-based semiconductors.